Blasticidin S Deaminase: A New Efficient Selectable Marker for Chlamydomonas reinhardtii - de Carpentier, Félix; Le Peillet, Jeanne; Boisset, Nicolas D.; Crozet, Pierre; Lemaire, Stéphane D.; Danon, Antoine (Frontiers in Plant Science, 2020)
Chlamydomonas reinhardtii is a model unicellular organism for basic or biotechnological research, such as the production of high-value molecules or biofuels thanks to its photosynthetic ability. To enable rapid construction and optimization of multiple designs and strains, our team and collaborators have developed a versatile Chlamydomonas Modular Cloning toolkit comprising 119 biobricks. Having the ability to use a wide range of selectable markers is an important benefit for forward and reverse genetics in Chlamydomonas. We report here the development of a new selectable marker based on the resistance to the antibiotic blasticidin S, using the Bacillus cereus blasticidin S deaminase (BSR) gene. The optimal concentration of blasticidin S for effective selection was determined in both liquid and solid media and tested for multiple laboratory strains. In addition, we have shown that our new selectable marker does not interfere with other common antibiotic resistances: zeocin, hygromycin, kanamycin, paromomycin and spectinomycin. The blasticidin resistance biobrick has been added to the Chlamydomonas Modular Cloning toolkit and is now available to the entire scientific community.